Asymptomatic Trauma Patients Screened for Venous Thromboembolism Have a Higher Risk Profile with Lower Rate of Pulmonary Embolism: A Five-Year Single-Institution Experience. Issue 2 (February 2020) - Johnson, Adam P.; Koganti, Deepika; Wallace, Adam; Stake, Seth; Cowan, Scott W.; Cohen, Murray J.; Marks, Joshua A.
Deep vein thrombosis (DVT) is linked to reimbursements and publicly reported metrics. Some hospitals discourage venous duplex ultrasound (VDUS) screening in asymptomatic trauma patients because they often find higher rates of DVT. We aim to evaluate the association between lower extremity (LE) VDUS screening and pulmonary embolism (PE) in trauma patients. Trauma patients admitted to an urban Level-1 trauma center between 2010 and 2015 were retrospectively analyzed. We characterized the association of asymptomatic LE VDUSs with PE, upper extremity DVT, proximal LE DVT, and distal LE DVT by univariate and multivariable logistic regression controlling for confounders. Of the 3959 trauma patients included in our study—after adjusting for covariates related to patient demographics, injury, and procedures—there was a significantly lower likelihood of PE in screened patients (odds ratio (OR) = 0.02, P < 0.001) and a higher rate of distal LE DVT (OR 11.1, P = 0.004). Screening was not associated with higher rates of proximal LE DVTafter adjustment for covariates (OR = 1.8, P = 0.193). PE was associated with patient transfer status, pelvis fracture, and spinal procedures in unscreened patients. After adjusting for covariates, we have shown that LE VDUS asymptomatic screening is associated with lower rates of PE in trauma patients and not associated with higher rates of proximal LE DVT. Our detailed institutional review of a large cohort of trauma patients over five years provides support for ongoing asymptomatic screening and better characterizes venous thromboembolism outcomes than similarly sized purely administrative data reviews. As a retrospective cohort study with a large sample size, no loss to follow-up, and a population with low heterogeneity, this study should be considered as level III evidence for care management.